Literature Review: Kemitraan Bidan dan Dukun Anak - Habibah, Minda; Rokhimawaty, Afita; Mardianah, Lia; Adnani, Qorinah Estiningtyas Sakilah (MEDIA ILMU KESEHATAN, 2024)
Background: In the community, traditional birth attendants (TBAs) have a significant societal role, especially for women. The WHO no longer recommends delivering a baby through TBAs due to the higher likelihood of maternal and infant mortality. A successful approach that has been effective in several countries for reducing maternal and infant mortality rates is the collaboration between TBAs and midwives.Objective: To analyze the collaborative association between midwives and TBAs to ascertain their objectives, obstacles, and possible resolutions.Methods: Literature review was employed in this research. The articles used were published from 2018 to 2023, encompassing five years, obtained from various databases including Pubmed, EBSCO, Science Direct, and Oxford Academy.Results: One hundred and ten articles were obtained and then screened. The final results were obtained from ten articles reviewed.Conclusion: The literature review highlights the significant societal role of midwives and traditional birth attendants. A major issue arose from the disparity in knowledge, proficiency, and perception. Enhancing collaboration can be accomplished through a multitude of methods, such as communication, training, role sharing, and incentives for TBAs.